The Influence of Emotional Intelligence on Job Burnout of Healthcare Workers and Mediating Role of Workplace Violence: A Cross Sectional Study - Cao, Yiyin; Gao, Lei; Fan, Lihua; Jiao, Mingli; Li, Ye; Ma, Yuanshuo (Frontiers in Public Health, 2022)
Objective: Globally, reducing job burnout among healthcare workers is considered a basic healthcare policy goal. Emotional intelligence, as an essential protective factor against psychosocial risks and a measurable positive psychological resource, still receives less attention in the process of reducing job burnout among healthcare workers.This study aims to explore the level of job burnout among healthcare workers who are victims of workplace violence in China, to examine the influence of emotional intelligence on job burnout among healthcare workers, and to verify the mediating role of workplace violence. Methods: A cross-sectional study was used to collect data from six tertiary public hospitals in three provinces (cities) in Eastern (Shandong and Tianjin) and Western (Gansu) China in 2018. A total of 2,450 questionnaires were distributed, with 2,061 valid questionnaires and a valid return rate of 88.95%. Of these, 825 healthcare workers had experienced workplace violence, accounting for 40.03% of the sample. A descriptive analysis, univariate analysis, Pearson correlation analysis, and mediated regression analysis were used to assess the level of job burnout among healthcare workers who are victims of violence, the effect of emotional intelligence on job burnout, and the mediating role of workplace violence. Results: The mean job burnout score of the healthcare personnel who were victims of violence was 35.56, with 70% suffering from moderate and high burnout. The emotional intelligence of healthcare workers is significantly negatively correlated with the degree of job burnout and workplace violence frequency. Further, workplace violence has a partial mediating effect on emotional intelligence and the two dimensions of job burnout (emotional exhaustion and depersonalization). Conclusions: This study is the first to combine emotional intelligence level, experiences of workplace violence, and job burnout levels of healthcare workers. We suggest that improving the emotional intelligence of healthcare staff has practical significance in reducing the level of job burnout directly and will reduce the incidence of burnout by reducing the frequency of violence (especially for emotional exhaustion and depersonalization). We provide specific and effective strategies for developing and guiding healthcare workers in the healthcare sector based on emotional intelligence.